Keratinocytes Isolated From Individual Cleft Lip/Palate Patients Display Variations in Their Differentiation Potential in vitro - Degen, Martin; Wiederkehr, Astrid; La Scala, Giorgio C.; Carmann, Christina; Schnyder, Isabelle; Katsaros, Christos (Frontiers in Physiology, 2018)
To gain more understanding of the complex molecular processes underlying cleft lip/palate (CLP), we established a unique human cell bank, consisting of keratinocytes and corresponding fibroblasts from individual CLP patients as a new study tool. After their careful characterization, we used such patient-derived cell cultures as well as control keratinocytes for in vitro differentiation and proliferation assays. Foreskin-derived control cells as a group showed significant higher induction of the late differentiation markers Loricrin and Filaggrin than the group of CLP patients-derived keratinocytes. Additionally, we detected great variations between individual CLP keratinocyte cell cultures in regard to their potential to terminally differentiate as assessed by the induction of Loricrin and Filaggrin. Primary patient cell cultures that did not properly differentiate, exhibited high proliferation rates. Moreover, we could correlate the expression levels of transcription factor IRF6 to the ability of individual cell cultures to terminally differentiate. Using clinically relevant, patient-derived cells, our results suggest that some of the genetic predispositions causing CLP might also lead to deficiencies in keratinocyte differentiation manifested in in vitro assays.